Characterization and evaluation of the natural resources of microriver basin cunyatupe - Contreras Málaga, Roberto (2009)
The microriver basin of Cunyatupe, located to the north of the city of Huaraz, in the department of Ancash-Peru; it presents/displays 5 zones of life, in addition to be within the White Mountain range of the Valley of Huaylas it has water in sufficient amount, to suitably maintain all the existing natural resources in this. With respect to the characterization of the microriver basin one was the following natural resources: Water, which it includes/understands a fluvial network that mainly has its origin in the different easts caused by the excessive erosion from cárcavas, Hidrobiológico where it was observed the presence of seaweed and worms like (Rhabditis Diplogasteroides, Dichotomosiphon, etc), Cattle dealer with bovine, ovine, equinos and pig greater cattles that is to say, Agricultural with the presence of cultivables species nutritional altoandinos like: barley, Pope, maize, wheat among others, fruit like: quince, apple, pacay and uvilla, Genetic or genetic aromatic like; Robust (Route graveolens), Ishmuna or muña (Minthostachys spp), etc, and genetic forages like: wild barley (Nassella Sp), Kikuyo (Pennisetum clandestinum), ichu (Stipa ichu), etc and finally, biological diversity with the presence of small lizards colilarga (Psammodromus algyrus), black picaflor (Metallura phoebe), among others inside d ela fauna and in addition species to flora lsecshi (cortaderia Sp), maguey (American Agave), ferns (Polistichium Sp), etc, Ecological  where one took encuenta the zones from life among others, and finally the Forest resource where they honor the eucalyptus (Eucalyptus Sp), alder (Alnus Sp), pine (Pinus Sp), capulí (Serotina Prunus), quenual (Polylepis Sp), etc. In the evaluation of the natural resources of the microriver basin one was grounds by capacity of greater use of class I to the VIII, with problems due to badly the related handling of water to its contamination, due to the raising of cattles, and badly use of the irrigation water, that causes the erosion.ike: retama (spartium junceum),